Diabetes imaging—quantitative assessment of islets of Langerhans distribution in murine pancreas using extended-focus optical coherence microscopy - Berclaz, Corinne (Optical Society of America, 2012)
Diabetes is characterized by hyperglycemia that can result from the loss of pancreatic insulin secreting β-cells in the islets of Langerhans. We analyzed ex vivo the entire gastric and duodenal lobes of a murine pancreas using extended-focus Optical Coherence Microscopy (xfOCM). To identify and quantify the islets of Langerhans observed in xfOCM tomograms we implemented an active contour algorithm based on the level set method. We show that xfOCM reveals a three-dimensional islet distribution consistent with Optical Projection Tomography, albeit with a higher resolution that also enables the detection of the smallest islets (≤ 8000 μm(3)). Although this category of the smallest islets represents only a negligible volume compared to the total β-cell volume, a recent study suggests that these islets, located at the periphery, are the first to be destroyed when type I diabetes develops. Our results underline the capability of xfOCM to contribute to the understanding of the development of diabetes, especially when considering islet volume distribution instead of the total β-cell volume only.